Pharmacokinetics of buprenorphine following constant rate infusion for postoperative analgesia in dogs undergoing ovariectomy. (May 2017) - Barbarossa, Andrea; Rambaldi, Julie; Giunti, Massimo; Zaghini, Anna; Cunto, Marco; Zambelli, Daniele; Valgimigli, Simond; Santoro, Francesco; Romagnoli, Noemi
Abstract: Objective: To investigate the pharmacokinetics of buprenorphine and its main active metabolite, norbuprenorphine, after administration of an intravenous loading dose followed by constant rate infusion (CRI) in dogs. Study design: Prospective, clinical study. Animals: A total of seven healthy dogs undergoing elective ovariectomy. Methods: Buprenorphine was administered as a loading dose (intravenous bolus of 15 μg kg −1 ) followed by CRI (2.5 μg kg −1 hour −1 for 6 hours). Moreover, intraoperative analgesia was supplemented by an intramuscular carprofen (4 mg kg −1 ) injection, administered prior to surgery, and by lidocaine, administrated through subcutaneous infiltration and through a splash on the ovarian vascular pedicle during surgery. Pain and sedation were scored for all animals throughout the 24-hour study period and rescue analgesia was administered when a visual analogue scale score was > 40 mm. Blood samples were collected from a jugular catheter at regular intervals, and plasma concentrations of buprenorphine and norbuprenorphine were determined by a validated liquid chromatography–tandem mass spectrometry method. Results: Buprenorphine showed a two-compartment kinetic profile. Maximum concentration was 23.92 ± 8.64 ng mL −1 at 1 minute (maximum time); elimination half-life was 41.87 ± 17.35 minutes; area under the curve was 486.68 ± 125.66 minutes ng −1 mL −1 ; clearance was 33.61 ± 13.01 mL minute −1 kg −1, and volume of distribution at steady state was 1.77 ± 0.50 L kg −1 . In no case was rescue analgesia required. Norbuprenorphine resulted below the lower limit of quantification in almost all samples. Conclusions and clinical relevance: The results suggest that a buprenorphine CRI can be a useful tool for providing analgesia in postoperative patients, considering its minor side effects and the advantages of a CRI compared to frequent boluses. The negligible contribution of norbuprenorphine to the therapeutic effect was confirmed.